Conclusions and implications for raising and sustaining high agricultural productivity in Africa - Benin, Samuel (International Food Policy Research Institute, 2016)
After more than a decade since the Comprehensive Africa Agriculture Development Programme (CAADP) was launched in 2003, many African countries have begun to articulate an agricultural transformation or Green Revolution agenda. These two approaches— like previous agriculture-led development frameworks, priorities, and strategies— hinge on a fundamental issue: how to raise and maintain high agricultural productivity. With the majority of the population living in rural areas and depending on agriculture for their livelihoods, and with typical household sizes of five to eight family members that together farm only 1– 3 hectares (ha) of land characterized by low agricultural productivity, it is easy to understand why rural poverty is so prevalent and persistent— and why raising agricultural productivity in a sustainable manner remains a fundamental development goal for Africa.